Estudio de la evaluación de desempeño laboral para la mejora en la gestión del personal administrativo EMAARS-EP Parroquia Ángel Pedro Giler - Loor Lucas, Verónica Andreina (2016)
The purpose of this research was the analysis of the management personnel performance in the Public Water company, Sewerage and Integrated Solid Waste Management Services of Bolívar, Junin, San Vicente, Sucre and Tosagua located in the Angel Pedro Giler parish via Tosagua; certain deficiencies in human resources were detected. The procedure was performed by reviewing job profiles and the examination of the structure of job performance during 2011 and 2014; the contrast of the results of such assessments and the proposed improvement plan were presented. Methods like inductive, deductive, descriptive, analytic and synthetic were used; observation techniques were used to post administrative staff profiles and performance evaluation conducted in 2011 and 2014; interview to the manager and specialist of human resources and a survey to 42 people of the administrative staff gave valuable information during the study. It was concluded that there are 28 job profiles for administrative staff prepared in accordance with the national legislation; the structure of assessments during 2011 and 2014 had no variation, and there was no big difference in the results. Finally the improvement plan was proposed to expose certain solutions to the anomalies presented.